Oral Comunication. Activities for the development of oral expression (Ogigia. Revista Electrónica de Estudios Hispánicos, 2017)
The use of efficient oral communication is key to success both at a personal level and in the public sphere. After reviewing the concept of oral communication and analyzing some difficulties of its development in the school world, we offer an intervention proposal, based on Bygate’s model of oral expression (1987), in which both knowledge and useful skills are developed to help students deal with different formal communicative situations.
Keywords: teaching oral communication; learning oral communication; groundwork